INNV-10. SAFETY OF APIXABAN FOR VENOUS THROMBOEMBOLISM PREVENTION IN PATIENTS WITH NEWLY DIAGNOSED GLIOBLASTOMA - Thomas, Alissa (Neuro Oncol, 2019)
Venous thromboembolism (VTE) impacts an estimated one in every three patients with malignant glioma (MG), resulting in increased morbidity and mortality. Despite the high prevalence and serious consequences of VTE, there is no outpatient standard of care prevention strategy. There have been three prospective clinical trials of VTE prophylaxis in patients with newly diagnosed MG, all of which used an injectable low molecular weight heparin (LMWH) product. We performed an open-label safety study of apixaban, a direct oral anticoagulant (DOAC), for VTE prevention in patients with newly diagnosed MG. All patients had surgery or biopsy two to twenty-one days prior to enrollment in the study. Patients were treated with apixaban 2.5 mg twice daily for up to 6 months. Peak and trough apixaban concentrations were measured at the beginning and end of treatment. Thirteen patients consented to the study and ten enrolled (2 screen-fail, 1 withdrawal). The patients have completed a mean of 4.5 cycles of apixaban (range 2 to 6, with 2 patients still undergoing treatment). There were no bleeding events while receiving apixaban. There were no hematologic or non-hematologic treatment-related adverse events. There were no VTE events observed in patients receiving apixaban. Two patients who came off treatment early due to disease progression developed VTEs after stopping prophylactic apixaban. Quality of life analysis is ongoing. In this pilot study we found that prophylactic dosing of 2.5 mg twice daily of apixaban was safe in the post-operative period for patients with newly diagnosed MG. Our preliminary results suggest that this may be a safe and effective prevention strategy for VTE prophylaxis in this high risk group of patients.